Novos anticoagulantes para a profilaxia do tromboembolismo venoso em cirurgia ortopédica de grande porte. Revisão sistemática de ensaios clínicos randomizados - de Alvarenga Yoshida, Ricardo [UNESP] (My University, 2012)
The use of new anticoagulants such as fondaparinux, rivaroxaban, dabigatran, apixaban and bemiparin has been studied for the prevention of venous thromboembolism (VTE) in orthopedic surgery. Objective: A systematic review of randomized clinical trials was conducted to assess the efficacy and safety of these new drugs for VTE prophylaxis in major orthopedic surgeries compared to enoxaparin. Data source: Double-blinded randomized trials were retrieved in an electronic search in medical literature published from 2000 to 2010. Data were assessed in RevMan v.5, the main computer software used by the Cochrane Collaboration. Data synthesis: Twelve clinical trials were selected. Four of them were on fondaparinux, three on rivaroxaban, three on dabigatran, one on apixaban and one on bemiparin. Two different dosage schemes of enoxaparin (40 mg 1x/day or 30 mg 2x/day, subcutaneous) were compared, depending on the study. Results: the results of primary efficacy - deep vein thrombosis (CVT), non-fatal pulmonary embolism (PE) and mortality as defined in the original articles - were favorable to fondaparinux (RR 0.50 [0.39-0.63] 95%CI) and to rivaroxaban (RR 0.50 [0.34-0.73] 95%CI) in comparison to enoxaparin, although the studies on rivaroxaban detected significant heterogeneity. The primary efficacy of dabigatran 220 mg, apixaban and bemiparin was similar to that of enoxaparin (RR 1.05 [0.87-1.26] 95%CI, RR 1.02 [0.78-1.32] 95%CI and RR 0.87 [0.65-1.17] 95%CI, respectively). Frequency of proximal DVT was lower with fondaparinux and rivaroxaban compared to enoxaparin (RR 0.31 [0.19-0.50] 95%CI and RR 0.68 [0.50-0.91] 95%CI, respectively), but significant heterogeneity was detected with rivaroxaban and dabigatran 220 mg. The frequency of symptomatic DVT was lower with the use of rivaroxaban compared to enoxaparin (RR 0.45 [0.27-0.77] 95CI) and similar to that of the other drugs. There were no significant differences as to pulmonary embolism frequency and mortality rates for the new anticoagulants in comparison to enoxaparin. The frequency of bleeding was significantly higher with fondaparinux compared to enoxaparin (RR 1.27 [1.04-1.55] 95%CI) and similar between other groups. At the end of the treatment, alanine aminotransferase (ALT) elevation was less frequent in the series that used dabigatran in comparison to those that used enoxaparin. Conclusions: The results of primary efficacy were favorable to fondaparinux compared to enoxaparin, but associated with a higher bleeding rate. Significant heterogeneity did not allow consistent conclusions as to the superiority of rivaroxaban for primary efficacy. The remaining anticoagulants presented primary efficacy non-inferior to enoxaparin. Symptomatic DVT was less frequent in the studies with rivaroxaban, and dabigatran was associated with a lower frequency of ALT elevation compared to enoxaparin. Apixaban and bemiparin had outcomes similar to those of enoxaparin, but results were based only upon one study each.
New anticoagulants for venous thromboembolism prophylaxis in major orthopedic surgeries. A systematic review of randomized controlled trials
Keywords: Meta-analysis; Orthopedics; Primary prevention; Pulmonary embolism; Venous thrombosis